Students’ perception on electronic food ordering in Kuala Terengganu / Nur Aisyah Syafiqah Muhammad Khairi Sham and Nur Farthiha Mohamad - Muhammad Khairi Sham, Nur Aisyah Syafiqah; Mohamad, Nur Farthiha (2018)
It is important for this study to determine the students’ perceptions on electronic food ordering either the students are understand and knowledge regarding this study. Sample populations for this study were among the students studied in the university around Kuala Terengganu. Two universities are chosen to conduct this study. In addition, the questionnaires analysis signified that the students do understand and have some knowledge about electronic food ordering.